1987
DOI: 10.1115/1.3248138
|View full text |Cite
|
Sign up to set email alerts
|

Forced Convection in a Duct Partially Filled With a Porous Material

Abstract: This paper presents a theoretical study of fully developed forced convection in a channel partially filled with a porous matrix. The matrix is attached at the channel wall and extends inward, toward the centerline. Two channel configurations are investigated, namely, parallel plates and circular pipe. For each channel configuration, both the case of constant wall heat flux and constant wall temperature were studied. The main novel feature of this study is that it takes into account the flow inside the porous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(105 citation statements)
references
References 0 publications
9
93
1
1
Order By: Relevance
“…12(c). At high k f /k s (1, 10 -1 ), a minimized Nu exists as Y i varies from 0 to 1, which is in accordance with the thermal equilibrium result of Poulikakos and Kazmierczak (Poulikakos & Kazmierczak, 1987). However, Nu monotonically decreases as Y i varies from 0 to 1 for low k f /k s , as in the case of metallic foams with high solid thermal conductivities.…”
Section: Fin Analysis Modelsupporting
confidence: 70%
“…12(c). At high k f /k s (1, 10 -1 ), a minimized Nu exists as Y i varies from 0 to 1, which is in accordance with the thermal equilibrium result of Poulikakos and Kazmierczak (Poulikakos & Kazmierczak, 1987). However, Nu monotonically decreases as Y i varies from 0 to 1 for low k f /k s , as in the case of metallic foams with high solid thermal conductivities.…”
Section: Fin Analysis Modelsupporting
confidence: 70%
“…However, assumption of a local thermal equilibrium existence between fluid and solid phases was considered in the most of former analytical and numerical works conducted. To name a few, the analytical studies presented by [32,33] as well as the numerical works done by [34,35]. Due to the significant difference existed between the thermal conductivities of fluid and solid phases in some porous media, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001 [44], the researchers investigated the heat transfer of the plate heat exchanger in the central arrangement between the plates and showed that the presence of porous material in the central makeup reduced the thickness of the boundary layer and consequently Increases heat transfer. Poulikakos and Kazmierczak's research [45] on compulsory displacement in a channel, which is partially occupied by porous material. The porous material is clinging to the channel wall.…”
Section: International Journal Of Advanced Engineering Management Anmentioning
confidence: 99%